2002
DOI: 10.1080/0036554021000026966
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-blinded, Placebo-controlled Trial of Early Administration of Recombinant Human Granulocyte Colony-stimulating Factor to Non-neutropenic Preterm Newborns Between 33 and 36 Weeks with Presumed Sepsis

Abstract: A randomized, double-blinded, placebo-controlled trial was conducted of early administration of recombinant granulocyte colony-stimulating factor (rGCSF) to 40 non-neutropenic, preterm infants between 33 and 36 weeks of gestational age with the diagnosis of presumed sepsis. The treatment group (n = 20) received 5 microg/kg per day of intravenous rGCSF once daily for 3 d and the control group (n = 20) received the same volume of physiological serum. Immediately before the first dose and on the 4th day, plasma l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 16 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…In consistent with our findings, Kucukoduk et al used 5 µg/kg/day of intravenous rG-CSF for 3 days, and indicated a significant increase in ANC meanwhile no change was observed in immature/total neutrophil ratios. They recorded the shortened length of time on the NICU in the treated infants (27). Moreover, Miura et al corroborated the increased level of neutrophil counts in premature neonates with EONS who were exposed to 10 µg/kg/day of intravenous rG-CSF for 3 days.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In consistent with our findings, Kucukoduk et al used 5 µg/kg/day of intravenous rG-CSF for 3 days, and indicated a significant increase in ANC meanwhile no change was observed in immature/total neutrophil ratios. They recorded the shortened length of time on the NICU in the treated infants (27). Moreover, Miura et al corroborated the increased level of neutrophil counts in premature neonates with EONS who were exposed to 10 µg/kg/day of intravenous rG-CSF for 3 days.…”
Section: Discussionmentioning
confidence: 87%
“…G-CSF is a prominent cytokine improving the function and growth of neutrophils. Despite the early evidence indicating the positive contribution of G-CSF to the treatment of EONS (26)(27)(28), there are controversies still exist on its application in infants, so further studies are required in either clinical or non-clinical (in vitro and in vivo) settings (29)(30)(31)(32). Considering the high incidence of sepsis in preterm infants and its subsequent morbidity and mortality (33,34), the objective of the present study was to evaluate the efficacy of the recombinant human G-CSF (rhG-CSF) administration on blood parameters (WBC, ANC, hs-CRP level and the ratio of immature to total neutrophils), and clinical parameters (mortality rate, adverse effects and duration of hospital stay) in preterm infants with EONS hospitalized at the NICU of Qaem Hospital in Mashhad, Iran.…”
Section: Introductionmentioning
confidence: 99%